Os significados da indisciplina na escola - Santos, Lucélia Gonçalves dos (2011)
This dissertation is an inquiry into the meanings referring to school indiscipline, made by a group of students, teachers and coordinators of a private and non-denominational school located in the city of Ponta Grossa, PR. School indiscipline is a complex phenomenon and one of the biggest pedagogical obstacles, which is able to damage the teaching-learning process and weaken the teacher-student relationship. Having as its objective to comprehend the meanings of indiscipline, made by that group of people, we have developed an inquiry that explores, in its theoretical frame of reference, a set of concepts thought out by Basil Bernstein. On the field research we have used the qualitative way of proceeding. The selection of the interviewed people followed the criterion of intentional sampling by maximum variation. Coordinators, teachers and students that participated in this research were divided into two groups. The first one, formed by those who recently joined the school, while the second was formed by those who were already at the school for a long time. As a method of analysis of the information, we chose the form of analysis of content from which the following categories for interpreting indiscipline have been derived: a) lack of socio-affective structures; b) disengagement with the environment of collective learning system; c) nullification of the teaching-learning process; d) result of the provisional teaching staff; e) reflection of the deficiency of the formative role performed by the family. The text is structured in the following way. First of all, we study some concepts created by Basil Bernstein in his theoretical studies. Then, we approach the building up of indiscipline in schools, arguing the concept of indiscipline under the light of the reflection of a group of theoreticians about it. Right after, we show some characteristics of the empirical research, of the sampling which was used and of the context which was been studied. Next we develop the analysis of the content of the interviews and in the last section we present the final considerations. This research offers us a series of readings about school indiscipline, which may make clear some of its possible meanings. We gave special emphasis to the notion of the indiscipline as the lack of socio-affective structures in the students. Moreover, it would also be a reflection of the provisional teaching staff, as well as a consequence of the nullification of the teaching-learning process. This inquiry also suggests that there is a crossing between family aspects and school aspects in the production of indiscipline, that is to say that there would be a discontinuity between the formative action of the family and the pedagogical practices of the school.